The Impact of Digital Technologies on Routine Tasks : Do Labor Policies Matter? - Almeida, Rita K.; Corseuil, Carlos H.L.; Poole, Jennifer P. (World Bank, Washington, DC, 2017)
There is a strong concern that technology is increasingly replacing routine tasks, displacing lower-skilled workers. Labor market institutions exist to protect workers from shocks but, by increasing labor costs, labor policy may also constrain firms from adjusting the workforce and, hence, from fully benefiting from technology adoption. This paper assesses the link between access to digital technologies and the demand for skills in the largest Latin American country, Brazil. Between 1996 and 2006, the country experienced a period of strong growth in Internet service provision, as well as in the enforcement of labor market regulations at the subnational level. The paper's empirical strategy exploits administrative data to assess the extent to which the adoption of digital technology affects employment and the skill content of jobs at the local level. In addition, the paper investigates whether the stringency of labor regulations influences this adjustment, by comparing the effect across industries subject to different degrees of enforcement of labor regulations. Using the fact that industries vary in the degree of reliance on digital technologies, the estimates suggest that digital technology adoption leads to a reduction in employment in local labor markets. The decrease in employment is larger for routine tasks, thereby shifting the composition of the workforce toward nonroutine, cognitive skills. However, and in contrast with labor policy intentions, the evidence points to the idea that labor market regulations differentially benefit the skilled workforce, particularly those workers employed in nonroutine, cognitive tasks.